2009
DOI: 10.17221/72/2009-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The effects of partial replacement of corn silage on biochemical blood parameters in lactating primiparous dairy cows

Abstract: ABSTRACT:The aim of this experiment was to investigate the effects of partial replacement of corn silage with long alfalfa hay and/or coarse chopped wheat straw on biochemical parameters in late lactating Holstein primiparous dairy cows. Twelve late lactating Holstein primiparous cows including four cows equipped with a rumen cannula, averaging 210 ± 20 days in milk and weighing 575 ± 50 kg were randomly assigned in a 4 × 4 Latin square design. During each of four 21-days periods, cows were fed four total mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…In spite of the importance of cattle in Turkey there has been a paucity of recent publications on the species in the international literature. Those that have been published include papers relating to animal health and disease (Cetinkaya et al, 2003;Aslantas et al, 2006;Temizel et al, 2009), production on state farms (Ekerden and Ozkutuk, 1990), some aspects of the biochemistry of milk (Polat, Gencoglu and Turkmen, 2009;Gurcan, 2011) and reports of small-scale experiments on meat production (Ozluturk et al, 2004;Unlu et al, 2008;Yuksel et al, 2009). The current paper aims to provide information on some of the main cattle populations of Turkey as well as some perceptions of their production and is one of a series (Wilson, Yilmaz and Ertugrul, 2011;Wilson, 2011a, 2011b) that will eventually cover all the nation's domestic animal species.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the importance of cattle in Turkey there has been a paucity of recent publications on the species in the international literature. Those that have been published include papers relating to animal health and disease (Cetinkaya et al, 2003;Aslantas et al, 2006;Temizel et al, 2009), production on state farms (Ekerden and Ozkutuk, 1990), some aspects of the biochemistry of milk (Polat, Gencoglu and Turkmen, 2009;Gurcan, 2011) and reports of small-scale experiments on meat production (Ozluturk et al, 2004;Unlu et al, 2008;Yuksel et al, 2009). The current paper aims to provide information on some of the main cattle populations of Turkey as well as some perceptions of their production and is one of a series (Wilson, Yilmaz and Ertugrul, 2011;Wilson, 2011a, 2011b) that will eventually cover all the nation's domestic animal species.…”
Section: Introductionmentioning
confidence: 99%
“…As well, it was considered that the dietary N to energy ratio, forage intake level, protein degradability, and dietary carbohydrate level can affect blood urea nitrogen content in ruminants (Hammond et al 1994). In addition, blood urea nitrogen, which is correlated with the solubility of fed nitrogen ingredients, is known as a good marker of rumen ammonia concentrations (Polat et al 2009). Our observations are in contrary to those reported in the research by Polat et al (2009), as they observed that replacement of corn silage had no signi cant effect on blood urea nitrogen content in lactating dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, blood urea nitrogen, which is correlated with the solubility of fed nitrogen ingredients, is known as a good marker of rumen ammonia concentrations (Polat et al 2009). Our observations are in contrary to those reported in the research by Polat et al (2009), as they observed that replacement of corn silage had no signi cant effect on blood urea nitrogen content in lactating dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of blood biochemical indicators revealed that incorporating AS and US silages in the steer diets resulted in normal blood values for most of the studied indicators when compared with the control diets (Duncan & Prasse 2003). However, concerning the increase in blood urea nitrogen concentrations in the ASTMR fed steers, it is well known that in ruminants, blood urea nitrogen can be influenced by dietary nitrogento-energy ratio, level of forage intake, protein degradability in the rumen, and dietary carbohydrate amount (Polat et al 2009). In the current experiment, both US and AS silage blends contained soluble protein; however, the addition of A. rouxii in the AS silage blend might have caused an increase in the ruminal ammonia concentrations in ASTMR fed steers, leading to higher blood urea nitrogen concentrations.…”
Section: Discussionmentioning
confidence: 99%